AB0873 ENDOTHELIAL DYSFUNCTIONIN PATIENTS WITH GOUT. RELATIONSHIP BETWEEN CARDIOVASCULAR RISK FACTORS. (June 2019) - Ilinykh, Ekaterina; Eliseev, Maxim; Volkov, Alexander
Abstract : Background: Patients with gout have a high risk of developing cardiovascular disease based on atherosclerosis. An early marker, and at the same time a risk factor of cardiovascular disease, is a violation of the vasoregulating endothelial activity. Objectives: To identify the relationship between cardiovascular risk factors and endothelial dysfunction (ED) in patients with gout. Methods: The study included 80 pts with gout. The criteria for inclusion were 1.Male 2.Age >55 years 3.Interictal period of arthritis 4.Absence of clinical signs of coronary artery disease 5.Absence of drug therapy. Vasoregulating endothelial activity was evaluated in all pts, 52 of them determined the carotid intima-media thickness (C-IMT). Flow-mediated (endothelium-dependent) dilatations (FMD), nitroglycerin-induced (endothelium - independent) dilatation (EID) were assessed by highresolution ultrasonography (D. Celermajer). A non-invasive ultrasound technique was used to measure C-IMT. All patients were diagnosed with serum total cholesterol (CHOL), subtypes (LDL-C, HDL-C), glucose (GLU), uric acid (SUA), hsCRP. Cardiovascular risk (CVR) was calculated. Statistical analysis was conducted using the applied programs package of descriptive statistics STATISTICA 12.0 (StatSoft.Inc., USA). Results: It was found that 41 (51.25%) pts had FMD less than 8%. A correlation was found between FMD and CVR (r= -0.28, p <0.05), age (r= -0.37, p<0.001), Body mass index (BMI) (r= -0.23, p<0.05). The links between FMD and LDL, GLU, SUA and with parameters reflecting the severity of gout were not revealed (p>0.05). C-IMT in pts was 0.7 (0.6-0.8) mm. 7 (14, 4%) pts had > 1.0 mm. A direct correlation was found between the C-IMT and the FMD (p <0.01), CVR (p <0.001), age (p <0.001), duration of gout (p <0.001), the number of joints affected for all time (p <0.005) and the frequency of arthritis in the last year (p <0.05). Correlation between C-IMT and LDL, GLU, SUA, hsCRB was not revealed (p>0.05). Conclusion: The ED, reflecting the risk of atherosclerosis, was found in 51.3% of patients with gout under the age of 55 years without clinical signs of coronary artery disease. The ED is associated with an increase in the CVR. C-IMT correlates with an increase in CVR and with parameters reflecting the severity of gout. References: [1] Celermajer D.S, Sorensen K.E., Gooch V.M. et al. Non-invasive detection of endothelial dysfunction in children and adults at risk atherosclerosis//Lancet.- 1992. - Vol.340. - P.1111-1115. [2] Corretti M.C., Anderson T.J., Benjamin E.J. et al. Guidelines for the ultrasound assessment of endothelial-dependent flow-mediated vasodilation of brachial artery//Jam. Coll. Cardiol. – 2002. - Vol.39. – P.257-265. Disclosure of Interests: None declared